2013
DOI: 10.1111/jocs.12199
|View full text |Cite
|
Sign up to set email alerts
|

Acute Intramural Hematoma of the Aorta Complicated by Spinal Cord Ischemia

Abstract: We present an unusual case of spinal cord ischemia from an acute type B intramural hematoma that was successfully treated with blood pressure elevation and drainage of cerebral spinal fluid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…To our knowledge, there have been only six other cases described in the literature besides our case (Table 2 ) [ 38 , 39 , 40 , 41 , 42 , 43 ]. For the first time, in 1996, Ferguson et al [ 38 ] reported a case of IMH with spinal cord ischemia in a 62-year-old hypertensive male.…”
Section: ⧉ Discussionmentioning
confidence: 85%
“…To our knowledge, there have been only six other cases described in the literature besides our case (Table 2 ) [ 38 , 39 , 40 , 41 , 42 , 43 ]. For the first time, in 1996, Ferguson et al [ 38 ] reported a case of IMH with spinal cord ischemia in a 62-year-old hypertensive male.…”
Section: ⧉ Discussionmentioning
confidence: 85%
“…Spinal cord infarction is rare, occurring in ~2% of cases of AD and is typically due to disruption of the vascular network supplying the spinal cord [7,18]. Ischaemic spinal cord injury has been described in a few cases of IMH, with some variability in symptom severity, but to the best of our knowledge BSS has never been described [8][9][10][19][20][21][22]. In this case, the findings on clinical examination correlate with the radiological findings, with the T12 sensory level corresponding to the thoracic segment of the IMH, and is near the region that was worst affected, and the evolving aortic ulcer.…”
Section: Discussionmentioning
confidence: 99%